1979
DOI: 10.1111/j.1365-2621.1979.tb03443.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory, Textural and Yield Properties of a Combination Ham Extended With Isolated Soy Protein

Abstract: Combination hams were prepared by injecting deboned ham muscles with brines containing solubilized isolated soy protein. The muscles were injected to levels of 30%, 45% or 60%, and then subjected to either 0 hr or 18 hr of intermittent massaging. The effects of massaging, isolated soy protein, and the level of injection on binding strengths, cooking yields and taste-panel scores were examined. Massaging and isolated soy protein improved both binding strength and cooking yield. increasing levels of injection de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Sensory panel evaluation data are shown in Table 5. The panelists consistently rated knockwurst containing 2.0% WPC more desirable (PcO.05) than that produced with 2.0% SPI, in agreement with Siegel et al (1979) who also found that panelists discriminated against the flavor of products which contained SPI. In all cases but one (aftertaste, in which no significant treatment difference was detected), knockwurst containing the 3.5% RNFDM was rated more desirable (PcO.05) than that containing 3.5% WPC.…”
Section: Results and Discussion Emulsion Stability Datasupporting
confidence: 81%
“…Sensory panel evaluation data are shown in Table 5. The panelists consistently rated knockwurst containing 2.0% WPC more desirable (PcO.05) than that produced with 2.0% SPI, in agreement with Siegel et al (1979) who also found that panelists discriminated against the flavor of products which contained SPI. In all cases but one (aftertaste, in which no significant treatment difference was detected), knockwurst containing the 3.5% RNFDM was rated more desirable (PcO.05) than that containing 3.5% WPC.…”
Section: Results and Discussion Emulsion Stability Datasupporting
confidence: 81%
“…The addition of MSB to restructured beef steaks may improve palatability and visual properties since MSB contains high amounts of heme pigments (Field, 1974). Textured soy protein (TSP) has been the most utilized extender because of a high protein content and good emulsification formation and stabilization properties (Siegel et al, 1979;Rakosky, 1974;Schweiger, 1974). However, the use of soy as an extender in meat systems may produce consumer acceptance problems (Williams and Zabik, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Replacing a portion of this premium meat with mechanically deboned meat (MDM) and or vegetable protein sources without detrimental alteration of the texture, flavor, and appearance of the rolls could result in substantial savings to the processor. Siegel et al (1979) noted that research on soy proteins has resulted in the development of nonmeat proteins with particular functional properties for use in meat products. The major objective has been to extend meat products with less expensive materials that do not alter nutritional properties, introduce off-flavors, or 1 Meat processing Research Unit.…”
Section: Introductionmentioning
confidence: 99%